2011
DOI: 10.1002/eat.20904
|View full text |Cite
|
Sign up to set email alerts
|

Personality pathology in purging disorder and bulimia nervosa

Abstract: Objective: To compare levels of personality pathology in women with purging disorder (PD), bulimia nervosa (BN), and controls and to compare women with PD and BN on associations between personality pathology and shared eating disorder features.Method: Women with BN (n 5 73), PD (n 5 48), and controls (n 5 64) completed interviews and self-report questionnaires.Results: BN and PD were associated with significantly greater personality pathology compared to controls. Cluster C symptoms and trait anxiety were grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 22 publications
4
27
3
Order By: Relevance
“…Also, PD did not differ from any other diagnosis concerning change in psychopathology or remission rates from start to follow-up, which supports studies finding no differences in treatment outcome between PD, AN and BN [20,21]. SBE has been suggested to be of special importance in defining PD [47], but in the present sample it was common in several diagnoses and not distinctive for PD. Taken together, the present results suggest no grounds for considering PD as a distinct ED.…”
Section: Discussionsupporting
confidence: 81%
“…Also, PD did not differ from any other diagnosis concerning change in psychopathology or remission rates from start to follow-up, which supports studies finding no differences in treatment outcome between PD, AN and BN [20,21]. SBE has been suggested to be of special importance in defining PD [47], but in the present sample it was common in several diagnoses and not distinctive for PD. Taken together, the present results suggest no grounds for considering PD as a distinct ED.…”
Section: Discussionsupporting
confidence: 81%
“…For example, despite a focus on PD for one of the studies included in analyses, 18 a latent PD group did not emerge. Instead, most cases of PD fell within LC1 along with cases of AN binge-purge subtype, BN purging and nonpurging subtypes, and BED that came from several studies contributing to analyses.…”
Section: Discussionmentioning
confidence: 99%
“…11, 17, 18 Importantly, the largest of these studies 11 contributed 192 (36%) participants and allowed for full variation of possible eating disorder symptoms ranging from DSM-IV AN binge-purge subtype to individuals free from eating disorder symptoms to permit evaluation of a dimensional model. Participants were between the ages of 18 and 53 years; mean (SD) age was 26.2 (7.3) years.…”
Section: Methodsmentioning
confidence: 99%
“…This is in line with a recent study of BN and PD that found the size of binge episodes explained additional variance in general and ED-related features beyond loss of control, and the relationship between loss of control eating, purging frequency, and depressive symptoms was stronger with larger binge sizes (Forney, Bodell, Haedt-Matt, & Keel, 2016). Furthermore, given suggestions that purging behavior may function to temporarily reduce aversive affective experiences associated with binge eating (Haedt-Matt & Keel, 2011), the lack of OBEs in PD may mitigate one of the primary functions of purging that serves to maintain and potentially exacerbate the behavior in other EDs characterized by OBEs.…”
Section: Discussionmentioning
confidence: 99%